Rapid and simple flow injection analysis tandem mass spectrometric method for the quantification of melphalan in a lipid‐based drug delivery system. (3rd August 2017) - Mohammed‐Saeid, Waleed; Michel, Deborah; Badea, Ildiko; El‐Aneed, Anas
Abstract : Rationale: The use of the anticancer drug melphalan is limited due to its poor water solubility. To address this limitation, it is incorporated within a novel delivery system using β‐cyclodextrin‐gemini surfactants (18:1βCDg). Methods: Herein, two fast and simple flow injection analysis/tandem mass spectrometric( FIA‐MS/MS) methods are developed for the quantification of melphalan (Mel) within the drug delivery system so that the solubilization efficiency of the system can be assessed. FIA‐MS/MS methods are developed using a triple quadrupole linear ion trap mass spectrometer, equipped with electrospray ionization (ESI) in the positive ion mode. A deuterated form of melphalan (melphalan‐d8) was used as an internal standard (IS). The methods were validated according to the FDA guidance. Results: A linearity in the range of 2–100 ng/mL and accuracy and precision below 15% were observed for all standard points and quality control samples. The intra‐ and inter‐day variations and freeze–thaw stability were within the acceptable range according to the criteria set by regulatory guidelines. On the other hand, other stability measures, such as room temperature stability and long‐term stability, did not meet the required guidelines in some cases, indicating the need for quick sample analysis upon preparation. Such a fact could have been overlooked if full method validation had not been performed. Conclusions: The developed methods were applied to determine the encapsulation/solubilization of the [18:1βCDg/Mel] delivery system. 18:1βCDg enhances the aqueous solubility of melphalan without the need for co‐solvent. The highest melphalan solubility was observed at a melphalan18:1βCDg/Mel complex molar ratio of 2:1. This study demonstrated that a fast analysis for the purpose of quantifying a chemically unstable drug, such as melphalan, is feasible and important for the development of commercial dosage forms.